Politik Birokrasi dalam Keamanan Pelabuhan di Indonesia: Sebuah Sebab Ketidakamanan - Muhammad Samy (Jejaring Administrasi Publik, 2022)
Abstract The economy of maritime states such as Indonesia rely on the sea, not only to extract natural resources but also as an essential medium for domestic and international trade. Focusing on the aspect of trade, it is important for maritime states such as Indonesia to have sea ports that function optimally. One of the determinants of the functionality of sea ports is port security. Despite being a maritime state, the security of sea ports in Indonesia is questionable. The presence of the so called â€œport mafiaâ€ and numerous accounts of crime in Indonesian sea ports as well as maritime traffic accidents indicate that Indonesia is not doing well enough to safeguard the security of her ports. This article scrutinizes the security of major international ports in Indonesia. Analysis is conducted using the bureaucratic politics theory framework. Based on the assumptions of the bureaucratic politics theory, this paper finds that the multiple actors involved in securing Indonesiaâ€™s major international ports have failed to function in a coordinated matter due to poor implementation of port security policy. The poor implementation of port security itself is caused by the competing interests of said actors. Â Keywords: Bureaucratic competition, bureaucratic politics, Indonesia, Port security, Sea ports